2018
DOI: 10.3389/fpsyg.2018.00609
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire-Based Maladaptive Decision-Coping Patterns Involved in Binge Eating Among 1013 College Students

Abstract: Binge Eating Disorder (BED), considered a public health problem because of its impact on psychiatric, physical, and social functioning, merits much attention given its elevation to an independent diagnosis in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). Similar with substance use disorders, some neuropsychological and personality constructs are potentially implicated in the onset and development of BED, in which poor decision-making has been suggested to facilitate overeati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
(57 reference statements)
0
24
2
Order By: Relevance
“…But paradoxically, most of these students could easily indulge themselves at university, staying away from parents and entrance exams. As a result, some mental disorders and behavioral disturbances (e.g., depression, anxiety, excessive gaming, smoking, shopping spree, binge eating and drinking) have been more and more salient in Chinese adolescents and young college students in recent decades (Liu and Zhou, 2002; Leung et al, 2008; Lian and Lin, 2008; Cao et al, 2011; Kieling et al, 2011; Yan et al, 2018). Our findings of the specific impulsivity traits involved in PIU (e.g., Negative Urgency) and cigarette smoking (e.g., Sensation Seeking), therefore, potentially designate a peculiar pathway to the prevention and intervention of certain problematic behaviors among Chinese college students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But paradoxically, most of these students could easily indulge themselves at university, staying away from parents and entrance exams. As a result, some mental disorders and behavioral disturbances (e.g., depression, anxiety, excessive gaming, smoking, shopping spree, binge eating and drinking) have been more and more salient in Chinese adolescents and young college students in recent decades (Liu and Zhou, 2002; Leung et al, 2008; Lian and Lin, 2008; Cao et al, 2011; Kieling et al, 2011; Yan et al, 2018). Our findings of the specific impulsivity traits involved in PIU (e.g., Negative Urgency) and cigarette smoking (e.g., Sensation Seeking), therefore, potentially designate a peculiar pathway to the prevention and intervention of certain problematic behaviors among Chinese college students.…”
Section: Discussionmentioning
confidence: 99%
“…A higher degree of delay discounting is described by a larger k -value. In our study, we adopted a culturally adapted Chinese version among college students (Sun and Li, 2011), which has been closely reported in our previous study (Yan et al, 2018). The k -values were calculated and log-transformed in order to get a normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…In this equation, k is a free parameter, with a larger k -value describing a higher degree of delay discounting. An adapted version of DDT among Chinese students ( 108 ) was used in this study, as reported in our previous studies ( 25 , 109 ). Examples of choices on this task are “A: receiving RMB ¥1000 now; B: receiving RMB ¥10000 one year later” and “A: receiving RMB ¥9000 now; B: receiving RMB ¥10000 one year later.” The k- value was calculated and log-transformed in keeping with the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Subjects have to choose between a smaller amount of money delivered “for sure” and a larger amount of money delivered probabilistically. Examples of choices are “A: $20 for sure; B: a 1-in-10 chance/10% of winning $80” and “A: $40 for sure; B: a 5-in-10 chance/50% of winning $100.” This task has been properly used in our previous study reported elsewhere ( 109 ). The degree of probability discounting is calculated by the equation V = A /(1+ h Θ), in which the free parameter h refers to the degree of probability discounting.…”
Section: Methodsmentioning
confidence: 99%
“…All of these facets of impulsivity have been investigated in relation to binge eating (both subclinical and full-blown BED). Yan et al, 2018). However, it is less clear whether this is driven by loss of control (LOC) eating or weight status.…”
Section: Impulsivitymentioning
confidence: 99%